A study on the awareness of using Virtual Reality on education in Universiti Utara Malaysia (UUM) - Lim, Wei Fong; Mustafar, Mastora (Universiti Utara Malaysia, 2020)
Nowadays, Virtual Reality (VR) technology, a new transformation tool that could help to improve the educational process towards highly competitive, increased productivity and consistent to innovate. This research is conducted by quantitative questionnaire method to explore the level of awareness and investigate the level of preparedness of the UUM student towards the use of VR technology for educational drives. The level of awareness and preparedness among the learners should be rose in order to be ready for the tide of the Fourth Industrial Revolution (IR4). Future research should include the factor that affect the level of awareness and the level of preparedness.